Electronic‐Structure Calculations of Cation‐Ordered II‐III Layered Double Hydroxides: Origin of the Distortion of the Metal‐Coordination Symmetry. Issue 30 (16th August 2017) - Jayanthi, K.; Vishnu Kamath, P.; Periyasamy, Ganga
Abstract : Cation ordering brings down the crystal symmetry and introduces distortion into the coordination polyhedra around the divalent cations. In particular, edge sharing of the differently sized [M(OH)6 ] polyhedra causes a non‐uniform distension of the array of hydroxy ions. The question arises as to whether this distortion has its origin in the Jahn–Teller distortion of metal coordination or a 2D "Peierls"‐type distortion of the array of hydroxy ions. To address this question, DFT calculations were performed on the sulfate‐intercalated [Cu–Cr], [Zn–Cr], and [Zn–Al] layered double hydroxides (LDHs). An analysis of the density of states shows that the distortion of the Cu 2+ coordination polyhedron is due to the Jahn–Teller effect, whereas the Zn 2+ coordination polyhedron in [Zn–Al] LDH likely suffers a "Peierls"‐type distortion. In the [Zn–Cr] LDH, electronic‐structure calculations do not predict any distortion in the metal coordination, which is in agreement with experimental results that show only a slight departure from ideal symmetry. Abstract : The comparison of the observed and computed structures of the [Cu–Cr] layered double hydroxide shows a bilayer arrangement of sulfate ions, along with water molecules in the interlayer region. The intercalated species form a hydrogen‐bonded network that screens the positive charge on the metal hydroxide layer.